DEFENSE POLICY BASED ON THE CONCEPT OF TOTAL DEFENCE - Radojević, Slobodan; Živanović, Vukojica (The Policy of National Security, 2024)
Total defence is a concept that should ensure the response of the state in situations caused by war and other extraordinary circumstances. This comprehensive approach of the state system's response requires that all segments of society as a whole actively act in order to preserve the sovereignty and security of the state. In order for a society to be able to respond positively to threats, challenges and risks, it is necessary that the strategy of deterrence be based on the concept of total defence. The historical beginnings of the establishment of the concept of total defence go back to the period after the Second World War, while the development of the concept intensified during the Cold War.The mentioned periods are characterized by an increase in the fear of aggression and potential occupation, which predicted that states would strengthen their own readiness for defence.The aim of this paper is to present, based on the experiences and examples of other countries, lessons learned that could be used to build the concept of total defense in the Republic of Serbia.The authors, finding important features of the application of the concept of total defense in countries around the world, tried to provide important lessons for strengthening military neutrality and building the concept of total defense of the Republic of Serbia.
Keywords: defence policy; military neutrality; the concept of total defence; deterrence strategy; the Republic of Serbia